The detection of the early stages of ageing in an LDPE+graphite composite by comparison of dielectric responses induced by sinusoidal and triangular signals - I. Petronijevic; K. Simonovic; F. Marinkovic; J. Dojcilovic; A. S. Luyt; D. Dudic (eXPRESS Polymer Letters)
This study describes the possibility of dielectric characterization of the initial stages of ageing in an low-density polyethylene (LDPE) + graphite composite, which is not possible using the standard method of dielectric spectroscopy. It is shown that the differences between the delay angles, Δφ = φTRI – φSIN, obtained using triangular and sinusoidal excitations on the composite samples, shows a maximum, and at the same time the position of this maximum shows more sensitivity to changes in the electrical properties of the material caused by ageing than other dielectric parameters. In order to clarify the applied methodology, a comparative analysis of the dielectric properties of other polymers poly(vinyl chloride) (PVC) and poly(vinyl alcohol) (PVA) and a conductive polymer composite (LDPE + carbon black) with respect to the application of sinusoidal and triangular electrical signals was carried out. Based on the presented results, we believe that the position of the peak in the frequency spectra of the difference between the delay angles obtained by using triangular and sinusoidal signals may be a suitable parameter for the dielectric characterization of polymeric materials.